Antibacterial, wet adhesive, and healing-promoting nanosheets for the treatment of oral ulcers. (17th March 2023) - Fu, Haijun; Yang, Jiayu; Shen, Zongshan; Zhang, Yong; Kuang, Shuhong; Li, Lifeng; Lin, Zhengmei; Shi, Xuetao
Abstract : With good physical properties, tissue adhesion, biocompatibility, and antibacterial properties, APCNs could effectively seal the ulcer surface, play an antibacterial role, reduce the inflammatory reaction, and accelerate the healing of the ulcer. Abstract : The severe pain caused by oral ulcers seriously affects food intake and speech, bringing great inconvenience in daily life. Drug-loaded patches are mostly used to treat oral mucosal diseases such as oral ulcers and oral lichen planus, but their effects are limited because of the influences of saliva and muscle movement. To enhance the adhesion of drug-loaded patches used in the oral cavity, we designed antimicrobial peptides (AMPs)-modified polycaprolactone (PCL)–collagen nanosheets (APCNs). The internal layer is a bioactive and antibacterial collagen layer modified with antimicrobial peptides. The backing layer is a hydrophobic PCL layer with good mechanical strength that can reduce external influences. We have characterized and tested the APCNs. First, the APCNs exhibited continuous and strong adhesion to irregular buccal mucosa surfaces under wet conditions and external force action. Antibacterial experiments showed that the APCNs had high antibacterial activity against both Gram-positive bacteria and Gram-negative bacteria. Moreover, the APCNs showed good biocompatibility and promoted the adhesion of fibroblasts in vitro . Furthermore, APCNs treatment accelerated ulcer healing in a Sprague Dawley rat oral ulcer model. Our study developed antibacterial, wet-adhesive, and healing-promoting PCL-collagen nanosheets and demonstrated that these nanosheets could be promising adhesive therapeutic agents for the treatment of oral mucosal ulcers.